Os fundamentos da ação coletiva passiva no ordenamento jurídico brasileiro - Viana, Flávia Batista (2009)
This study aims to demonstrate the foundations that support the place of defendant class actions in the Brazilian legal system despite any legislative amendment. For both, were prepared and legal research literatures, using inductive methods, historical and comparative, so that, by national and foreign literature, could be considered the most important reasons to validate the place of collective actions passive. The first chapter is devoted to an overview of class actions from the Ancient Age to the present day to explain why the defendant class action was not developed. It was foreshorten a brief history on the subject in law the U.S. and Brazil, and on this, were still addressed the aspects which are the main theme. The second chapter is an overview of the mapping class actions in several orders foreign to demonstrate that the relevance of the issue is not exclusively Brazilian. Even were moot the concept and some classifications of defendant class actions, and were presented the foundations of several orders that support the defense of defendant class actions in our country without any legislative change. The last chapter focused on the analysis of some procedural issues crucial to the place of defendant class actions, such as adequacy of representation and the res judicata, and the proposals of legal rules for defendant class actions